Conjuntura da agricultura irrigada no Estado do Amapá entre os anos de 2006 e 2017 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The irrigation technique is of fundamental importance for agricultural production, as it contributes to increased productivity and favors food stability. Therefore, the objective was to evaluate the situation of irrigated agriculture in the state of Amapá between the years 2006 and 2017. The research was carried out covering the 16 municipalities in the state of Amapá, carrying out data collections regarding irrigation through the IBGE System Automatic Recovery. The municipality of Porto Grande had the largest number of agricultural establishments using irrigation in 2006, while Macapá-AP was the highlight in 2017, followed by Santana-AP. Most agricultural establishments adopted alternative irrigation methods to conventional ones, both in 2006 and in 2017. In terms of irrigated area, alternative methods were responsible for most in 2006, while in 2017 the surface method stood out. As for the average size of irrigated areas, in 2017 most establishments using alternative and sprinkler methods had less than 1 hectare of cultivation. It is emphasized that in 2006 the number of establishments with permanent farming activities in all methods was predominant, followed by horticulture and floriculture. In 2017, temporary crops stood out, followed again by horticulture and floriculture. It was found that in 2006 most establishments with sprinkler and localized irrigation had received technical guidance, while in 2017 this scenario was not observed for any of the methods, showing a lower relative supply of this service. Women are a minority in the practice of irrigation in Amapá, but there is a proportional increase between the years 2006 and 2017, noting an advance in the use of this technique in the establishments conducted by them.
Keywords: Agricultura - Estatísticas - Amapá; Irrigação agrícola - Amapá; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA